Does Surgeon Sex Matter?: Practice Patterns and Outcomes of Female and Male Surgeons. Issue 6 (June 2018) - Sharoky, Catherine E.; Sellers, Morgan M.; Keele, Luke J.; Wirtalla, Christopher J.; Karakousis, Giorgos C.; Morris, Jon B.; Kelz, Rachel R.
Abstract : Objective: We sought to compare postoperative outcomes of female surgeons (FS) and male surgeons (MS) within general surgery. Summary of Background Data: FS in the workforce are increasing in number. Female physicians provide exceptional care in other specialties. Differences in surgical outcomes of FS and MS have not been examined. Methods: We linked the AMA Physician Masterfile to discharge claims from New York, Florida, and Pennsylvania (2012 to 2013) to examine practice patterns and to compare surgical outcomes of FS and MS. We paired FS and MS operating at the same hospital using cardinality matching with refined balance and compared inpatient mortality, any postoperative complication, and prolonged length of stay (pLOS) in FS and MS. Results: Overall practice patterns differed between the 663 FS and 3219 MS. We identified 2462 surgeons (19% FS, 81% MS) at 429 hospitals who met inclusion criteria for outcomes analysis. FS were younger (mean age ± SD FS: 48.5 ± 8.4 years, MS: 54.3 ± 9.4y; P < 0.001) with less clinical experience (mean years ± SD FS: 11.6 ± 8.3 y, MS: 17.6 ± 10.0 years; P < 0.001) than MS before matching. FS had lower rates of inpatient mortality (FS: 1.51%, MS: 2.30%; P < 0.001), any postoperative complication (FS: 12.6%, MS: 16.1%; P < 0.001), and pLOS (FS: 18.4%, MS: 20.7%; P < 0.001) before matching. After matching, FS and MS outcomes were equivalent. Conclusion: Surgeon practice patterns vary by sex and experience. FS and MS with similar characteristics who treat similar patients at the same hospital have equivalent rates of inpatient morality, postoperative complications, and prolonged length of hospital stay. Patients should select the surgeon who is the best fit for them regardless of sex. Abstract : Supplemental Digital Content is available in the text